Star and star fish: an experiment with memory drawing and drawing with mental image stimulation - Miranda, Eva Rolim; Coutinho, Solange Galvão (InfoDesign, 2010)
The main objective of this paper is to compare the differences between memory drawing and drawing with mental image stimulation, analyzing the differences and similarities of those processes according to Coutinho’s (1998) analytical model. It was made a review on several studies that contributed with that theme. To verify the differences the Darras (1996) experiment was replicated with twenty participants from the Henfil Municipal School – Várzea – Recife. This experiment had two phases, the first involved memory drawing and the second involved drawing with stimulation of mental image. Twelve objects were drawn by the subjects, but on this paper we exemplify those using the star-fish. The methodology used was ethnographical and the data was collected at the school. The data was treated using the Coutinho's (1998) model. The most of the data was examined qualitatively, although some data was treated quantitatively.